Effect of hydrofluoric acid etching duration on the roughness and flexural strength of a lithium disilicate-based glass ceramic - Zogheib, Lucas Villaça; Della Bona, Alvaro; Kimpara, Estevão Tomomitsu [UNESP]; Mccabe, John F. (FapUNIFESP (SciELO), 2011)
The aim of this study was to examine the effect of different acid etching times on the surface roughness and flexural strength of a lithium disilicate-based glass ceramic. Ceramic bar-shaped specimens (16 mm x 2 mm x 2 mm) were produced from ceramic blocks. All specimens were polished and sonically cleaned in distilled water. Specimens were randomly divided into 5 groups (n=15). Group A (control) no treatment. Groups B-E were etched with 4.9% hydrofluoric acid (HF) for 4 different etching periods: 20 s, 60 s, 90 s and 180 s, respectively. Etched surfaces were observed under scanning electron microscopy. Surface profilometry was used to examine the roughness of the etched ceramic surfaces, and the specimens were loaded to failure using a 3-point bending test to determine the flexural strength. Data were analyzed using one-way ANOVA and Tukey's test (α=0.05). All etching periods produced significantly rougher surfaces than the control group (p<0.05). Roughness values increased with the increase of the etching time. The mean flexural strength values were (MPa): A=417 ± 55; B=367 ± 68; C=363 ± 84; D=329 ± 70; and E=314 ± 62. HF etching significantly reduced the mean flexural strength as the etching time increased (p=0.003). In conclusion, the findings of this study showed that the increase of HF etching time affected the surface roughness and the flexural strength of a lithium disilicate-based glass ceramic, confirming the study hypothesis.
Keywords: CAD/CAM; Flexural strength; Hydrofluoric acid; Lithium disilicate glass ceramic; Roughness; hydrofluoric acid; lithia disilicate; chemistry; dental acid etching; dental bonding; dental care; materials testing; methodology; pliability; randomization; scanning electron microscopy; surface property; time; tooth prosthesis; Acid Etching, Dental; Dental Bonding; Dental Porcelain; Dental Stress Analysis; Hydrofluoric Acid; Materials Testing; Microscopy, Electron, Scanning; Pliability; Random Allocation; Surface Properties; Time Factors